SIFAT VENIR DAN KAYU LAPIS 9 JENIS KAYU DARI JAWA BARAT - M I lskandar; Suwandi Kliwon; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1991)
A  study result on the suitability of  9 wood species  from   West  Java  as raw material for  veneer and plywood is reported in this paper study  conaisted of  log peeling characteristic, veneer property   and some  physical/ mechanical properties  of plywood  (triplex and multiplex):All  of the logs  from 9 wood species could be peeled in cold condition, producing 1.5 mm veneer at a cuting angle between 90°30-91°30. The average shrinkage of veneer  is  7.21%, with a minimum of 4.08% (Enteroloblum)  and maximum 10. 75% (keruing). Veneer swelling from oven-dry to air-dry  condition varied between 2.04% (Enterolobium)  and 4.28%  (Damar)  with an average of  2.93%.The bonding strength of plywood  from 6 wood species (66%.) conform with the Indonesian standard fo  type 11 or water resistant, all wood  species conform with Japanese and German standard.The specific gravity of multiplex (0,60) is  higher than triplex (0,58). Some mechanical properties of multiplex are higher than triplex.